2020
DOI: 10.1016/j.joca.2020.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Development of osteoarthritis in patients with degenerative meniscal tears treated with exercise therapy or surgery: a randomized controlled trial

Abstract: To evaluate progression of individual radiographic features five years following exercise therapy or arthroscopic partial meniscectomy as treatment for degenerative meniscal tear. DesignRandomized controlled trial including 140 adults, aged 35-60 years, with a magnetic resonance image verified degenerative meniscal tear, and 96% without definite radiographic knee osteoarthritis. Participants were randomized to either 12-weeks of supervised exercise therapy or arthroscopic partial meniscectomy. The primary outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 40 publications
2
42
0
Order By: Relevance
“…We pooled data from both treatment groups to improve precision and statistical power, which means that we had a heterogeneous sample with respect to treatment. Even though no between-group differences have been detected for changes in patient-reported outcomes in the OMEX trial 5,20 or in several other high-quality randomized controlled trials, 13,39,44 we cannot discount the possibility that trajectories and associated prognostic factors differ between the 2 treatments.…”
Section: Limitationsmentioning
confidence: 88%
“…We pooled data from both treatment groups to improve precision and statistical power, which means that we had a heterogeneous sample with respect to treatment. Even though no between-group differences have been detected for changes in patient-reported outcomes in the OMEX trial 5,20 or in several other high-quality randomized controlled trials, 13,39,44 we cannot discount the possibility that trajectories and associated prognostic factors differ between the 2 treatments.…”
Section: Limitationsmentioning
confidence: 88%
“…We thank Yu et al for their interest in our recent publication entitled "Development of osteoarthritis in patients with degenerative meniscal tears treated with exercise therapy or surgery: a randomized controlled trial" 1 .…”
Section: Dear Editormentioning
confidence: 99%
“…We certainly agree with the authors that MRI findings are no cause for treatment, surgical or non-surgical. As described in the inclusion criteria, all patients had to be considered eligible for surgery 1 . We would like to clarify that one experienced orthopedic surgeon at Oslo University Hospital or one experienced orthopedic surgeon at Martina Hansens Hospital confirmed eligibility based on patient history, physical examination, and MRI findings 2 .…”
Section: Dear Editormentioning
confidence: 99%
“…Evidence from randomized controlled trials (RCT) has suggested that partial meniscectomy may not be superior to non-surgical care alone or sham surgery, but some trials had important study design limitations and high cross-over rates [1,7,27,32,33,35,36]. Nonetheless, expert consensus statements and professional societies recommend partial meniscectomy for patients with irreparable meniscus tears and mechanical knee symptoms that are refractory to at least 3 months of non-surgical care [5,19].…”
Section: Introductionmentioning
confidence: 99%